O uso da calculadora e o pensamento matemático avançado: uma análise a partir das situações de aprendizagem nos Cadernos do Professor de Matemática da Secretaria da Educação do Estado de São Paulo - Prado, Sonia de Cassia Santos (2012)
The aim of this documentary qualitative research is to investigate the insertion of the use of the calculator in Learning Situations proposed to students from Ensino Fundamental II (from 5th to 9 th grade), from the São Paulo State public school in Teacher s Notebooks , using the Advanced Mathematical Thinking. In order to do so, we used the three main chronological points from Content Analysis, pre-analysis, exploring the material and treating the results, inference and interpretation, to investigate the given orientations about the approach from the Learning Situations from the Mathematics Teacher s Notebooks (2009), distributed to all the state s teaching public network. The motivation to choose this theme has come from the fact that the usage of calculators as a resource to learning Maths is still not enough, even though it is known that they help to investigate problem-situations. The usage of calculators is motivated in the official documents that guide the technologies in Ensino Fundamental II. Thus, we have searched elements in ideas of Advanced Mathematical Thinking on how a Mathematical concept can be understood by the student, according to the interaction of the mental processes of the components: representation, visualization, generalization, synthesis and abstraction from the use of the calculator. To reinforce the grounds for this research, we have followed the orientations from official documents: Parâmetros Curriculares Nacionais do Ensino Fundamental II (1998), Proposta Curricular de Matemática (2008), Currículo de Matemática (2010), and Mathematics Teacher s Notebooks (2009) and in researches made about the utilization of this pedagogical tool. Subjectively, we present the analysis of Learning Situations , by using previously established categories that, in some point of its sequential development, proposed the utilization of this pedagogical resource, seeing which of the components of Advanced Mathematical Thinking could be developed. We have found, among 64 Learning Situations proposed to the grades from Ensino Fundamental II, 8 activities that, along by its development, asked to use this resource in some section, and the representation is in 8 activities, the visualization is in 6 activities, the generalization is in 5 activities, the synthesis is in 8 activities and the abstraction is in 7 activities